The Nature of Multicultural Education in Indonesia: A Perspective on Islamic Education - Darmawati Jufri; St. Wardah Hanafie Das (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2024)
Indonesia is a country with a vast diversity of cultures, religions, and ethnicities, which makes it one of the most pluralistic societies in the world. Multicultural education is present as a strategic approach to instill the values of tolerance, inclusion, and social harmony in the midst of this diversity. This article explores the nature of multicultural education in Indonesia from the perspective of Islamic education, which emphasizes respect for differences as part of the sunnatullah. Through literature research methods, this article discusses the concept, implementation, and challenges of multicultural education in the national education system. The results of the study show that multicultural education can be implemented through the development of diversity-based curriculum, teacher training to manage multicultural classrooms, and the creation of an inclusive educational environment. The Islamic perspective provides a strong philosophical and normative foundation to support multicultural education, such as the teachings of the Qur'an and Hadith that emphasize the importance of tolerance and intercultural dialogue. However, the implementation of multicultural education faces challenges, including cultural resistance from exclusivity groups and limited resources in schools, especially in remote areas. This article recommends strengthening the socialization of multicultural values, developing contextual teaching materials, increasing teacher training, and allocating adequate resources as solutions to overcome these challenges. By integrating Islamic values in multicultural education, Indonesia can build a generation that is tolerant, inclusive, and able to maintain social harmony in the midst of diversity. This article contributes to enriching the discourse of multicultural education and offers practical solutions for its implementation.